An Improved Multi-Hop-Enabled Energy Efficient MAC Protocol for Underwater Acoustic Sensor Networks - Mozumder, Tomal Kumer; Waheed, Sajjad (European Scientific Journal, ESJ, 2017)
Packet collisions occurred by hidden and local nodes in multi-hop enabled underwater acoustic sensor networks (UWASNs) have effect on throughput, energy efficiency and end-to-end delay. Existing Multi-HopEnabled Energy Efficient MAC Protocol for Underwater Acoustic Sensor Networks (MHEE MAC) utilized a double-phase contention resolution mechanism, which causes visit multiple time slot and energy overhead. In this paper, we propose a MAC protocol that use contention resolution mechanism with unique priority to provide energy efficiency. First, local nodes are eliminated comparing their priority and later, hidden nodes are mitigated. A simulation of proposed protocol is also developed to analyze the performance. Results obtained through simulation show that the proposed protocol achieves significantly lower energy consumption, reserve more energy and more stable throughput compared to MHEE-MAC, T-Lohi and slotted floor acquisition multiple access (S-FAMA).